Gender beliefs framed on culturo-techno-contextual approach about learning of difficult STEM concepts in African Secondary Schools - Gbeleyi, Olasunkanmi A; Potokri, Onoriode Collins (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
This study employed a survey and quasi-experimental design. The purpose of this study is to find out the efficacy of the lecture method, and culturo-techno-contextual approach on students’ gender and attitude to logic gate. Results obtained from the survey in the first phase revealed logic gate, problem-solving skills, and machine language as the most difficult topic in computer studies. The second phase is a quasi-experimental design guided by two research questions with three public junior schools (equivalent to 8th grade) in Nigeria and Ghana. 38% (80) of the respondents were males while 62% (133) were females. Logic gate attitude (LGSAQ), and the student interview guide were used to collect data for the study. The data gathered was subjected to analysis of covariate (ancova), and the results showed no significant difference in students’ gender taught using the culturo-techno-contextual approach, and the lecture method [F (1, 210) = 2.18; p>.05]. Based on the findings of the study, CTCA is recommended to computer studies teachers in Africa and beyond as a possible tool to set their teaching methods within culturally relevant and technologically appropriate contexts.
Journal article published in African Perspectives of Research in Teaching & Learning (APORTAL) Vol 7 (1) (2023)
Keywords: Attitude; Gender; Culturo-Techno-Contextual Approach; STEM; Attitude (Psychology); Education, Primary; Technological innovations; Teachers; Computers -- Study and teaching